Mechanism for the Inhibition of Dewetting in Polymer Thin Films by Interface Segregation of Single-Chain Nanoparticles (Communications in Computational Chemistry, 2025)
The inhibition of dewetting in polymer thin films (PTFs) is crucial for their practical applications. Through moleculardynamics simulations, we elucidate the mechanism of interface segregation of single-chain nanoparticles (SCNPs) in inhibitingPTF dewetting. Our study provides atomic-level insights into three key aspects: (1) how SCNP segregation affects the contactangle, (2) how it influences the orientation of matrix chains at the interface, and (3) how the interaction between solvent moleculesand cross-linkers within SCNPs influences the dewetting behavior. By employing static droplet and dynamic pre-punched filmmodels, we systematically investigate the effects of SCNP doping concentration and cross-linker-solvent interaction strength. Ourresults demonstrate that SCNP segregation significantly alters the orientation of linear polymer chains at the interface. In purepolymer films, chain ends preferentially accumulate at the interface due to entropic effects, leading to parallel chain conformations.However, SCNP segregation suppresses this effect, promoting more vertical chain orientations. Furthermore, we find that weakercross-linker-solvent interactions promote SCNP segregation at the substrate interface, leading to more effective dewettinginhibition. These findings provide fundamental understanding and practical guidance for designing stable polymer thin filmsthrough nanoparticle doping.
Keywords: polymer thin films; single-chain nanoparticle; dewetting inhibition